The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.33306/mjssh/200
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical Strategies for Appeal to Logos in Research Abstracts: An Analysis of Rhetoric

Abstract: This study examined the use of two rhetorical strategies - nominal-numerical types of supporting data and lengthy complex types of sentences due to their rhetorical appeal to Aristotelian logos in the writing of research abstracts. A total of 480 research abstracts sampled from English as a Native (ENL) and English as a Second Language (ESL) were analysed with LIWC2015 software application and Readable.com online applications. Guided by the Connor’s (1996)5 Contrastive Theory of Rhetoric with the integration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The language mastery challenged the textuality, which limited the authors' academic language expressions and strategies. Some previous studies identified this phenomenon, for example Mohamad et al (2022) and Oravițan et al (2022). Textuality might be caused by the authors English proficiency and the awareness of academic writing convention (Ahmad, 2022;Amnuai, 2019;Fang, 2021;Solikhah, 2016).…”
Section: Textualitymentioning
confidence: 93%
“…The language mastery challenged the textuality, which limited the authors' academic language expressions and strategies. Some previous studies identified this phenomenon, for example Mohamad et al (2022) and Oravițan et al (2022). Textuality might be caused by the authors English proficiency and the awareness of academic writing convention (Ahmad, 2022;Amnuai, 2019;Fang, 2021;Solikhah, 2016).…”
Section: Textualitymentioning
confidence: 93%
“…As discussed in the earlier section of the research, the lack of differences in the use of academic research rhetorical features would suggest the near-native English level of academic rhetoric. This argument was substantiated by Vinkers et al (2015); Mohamad (2022) and Mohamad et al (2022) based on their studies of academic research abstract compositions. The lack of significant differences in the use of negative words and phrases between native and non-native English research abstracts would demonstrate the near native English rhetoric of Malaysian nonnative English writers in composing their research abstracts to emotionally appeal to the readers.…”
Section: Emotive and Passive Tone Of Voice In Academic Research Compo...mentioning
confidence: 95%
“…However, marked differences were not shown in the use of neutral words. Based on the near-native rhetoric postulated by Mohamad et al (2022), the lack of differences in these rhetorical features suggested the non-native English writers' nearnative English levels of rhetoric in academic research composition.…”
Section: Past Studiesmentioning
confidence: 99%
“…This was probably due to the compositional act of summarising the research work performed at the last stage of the research writing process without due and fair degree of academic concern when it should have been the most critical section to be given the most attention and consideration in terms of the organisational move structure. It would be used as the main window firstly presented to invite the readership into an entire article which was underscored by Connor (1996) and Mohamad et al (2022) that major variations of the commonly known structure with disorganised or missing parts, would most likely compromise the interest of the readers to give their time and commitment to read the full papers.…”
Section: Problem Statementmentioning
confidence: 99%
“…The rhetoric of academic research writing is imbued with many rhetorical and linguistic features. Mohamad et al (2022) identified these features to be prevalent at the various levels of operational compositions, such as the lexical, phrasal, sentential, and organisational or discourse levels. A logically arranged presentation of research ideas at the genre-based discourse level reflects a writer's mental structure and thought process in transferring the information of their research points in a well-thought-out and analytically systematised form.…”
Section: Introductionmentioning
confidence: 99%